A WEB SERVICE ARCHITECTURE FOR MOBILE ACADEMIC INFORMATION SYSTEM: A CASE STUDY OF LAMPUNG UNIVERSITY - Kurnia Muludi; Saiful Anwar; Dwi Sakethi; Akmal Junaidi; Wartariyus Wartariyus (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2022)
Lampung University has many information systems with many different platforms and programming languages. This condition degraded the performance of each system. In this case study, we develop a web service that can increase collaboration between systems and between business units. Through a combination of Django REST Framework and OAuth 2.0 technology, it is shown that various platforms and applications can work together. While Django Rest Framework provides an excellent web service, OAuth strives to address the shortcomings of proprietary authentication protocols by creating universal and interoperable authorization mechanisms between service units. To prove the concepts, we implemented web service for an Android application client.Keywords: Web Service, Django REST Framework, OAuth 2.0, Android Application, Application Programming Interface